LARVICIDAL ACTIVITY OF ESSENTIAL OILS AGAINST Aedes aegypti and Culex quinquefasciatus LARVAE (DI PTERA: CULICIDAE) - F. Manzoor; K. B. Samreen; Z. Parveen (Journal of Animal and Plant Sciences, 2013)
Five essential oils from various parts of five plant species i.e. Acorus calamus ,Mentha arvensis, Ocimum basilicum, Saussrea lappa and Cymbopogan citrates were investigated for their larvicidal property against Aedes aegypti (L.) and Culex quinquefaciatus (Say) larvae. Essential oils were obtained by steam distillation method. The mosquitoes were reared in laboratory by maintaining conditions and twenty late 3rd instar larvae of Ae. aegypti (L.) and Cx. quinquefaciatus (Say) were exposed to different concentrations of essential oils ranging from 1.95-1000.00ppm. The larval mortality was observed after 24 hours under the laboratory conditions. Results showed that all the tested essential oils produced significant larval mortality against two mosquito species. However, the highest larvicidal activity was observed in the essential oil from O. basilicum against Ae. Aegypti (L.) and Cx. quinquefaciatus (Say) with LC50 values 75.35 ppm and 92.30 ppm respectively. However the LC50 values for A. calamus, M. arvensis, S. lappa and C. citrates against Ae. Aegypti (L.) were 99.41, 114.33,128.89 and 136.28 ppm respectively and against Cx. quinquefaciatus (Say) were 107.81, 112.18, 141.43 and 148.54ppm respectively. No mortality was observed in controls. According to the larvicidal activity of essential oils against Ae. aegypti (L.) and Cx. quinquefaciatus (Say), the oils were arranged in the following ascending order of preference i.e. O. basilicum> A. calamus> M. arvensis> S. lappa> C. citrates. From the results, it can be concluded that essential oils had excellent potential for controlling mosquito larvae in Pakistan.
Keywords: essential oil; Aedes aegypti; Culex quinquefasciatus